Extended Near‐Infrared Photovoltaic Responses of Perovskite Solar Cells by p‐Type Phthalocyanine Derivative. (9th October 2022) - Zhang, Zhenhu; Liu, Hongli; Wang, Shirong; Bao, Huayu; Zhang, Fei; Li, Xianggao
Abstract: The absent photo‐response in near‐infrared (NIR) light (>800 nm) of lead‐based perovskite solar cells (PSCs) limits the further improvement of their power conversion efficiency (PCE). Here, a narrow bandgap p‐type phthalocyanine derivative (Copper(II) 2, 3, 9, 10, 16, 17, 23, 24‐octakis((4‐(bis(4‐methoxyphenyl)amino)phenyl)ethynyl)phthalocyanine –8TPAEPC) with NIR absorption is synthesized to extend the photovoltaic response of perovskite to 850 nm. After doping the 8TPAEPC into the perovskite photoactive layer, the perovskite crystal quality is improved, resulting in its good electrical conductivity and less surface defects. Furthermore, the molecules stacking on the grain boundaries construct the charge transportation paths, as well as the p–n bulk heterojunction with enhanced built‐in potential. The target PSCs are optimized with notably enhanced PCE from 20% up to 22.10%, and excellent stability that is over 80% of the initial level at 70–80% relative humidity can be maintained for more than 500 h, benefiting from the improved hydrophobicity of 8TPAEPC. In addition, 8TPAEPC also serves as a dopant‐free, highly carrier‐mobile, and moreover, NIR‐responsive hole transport layer (HTL) with boosted PCE of 20.42% that reaches state of the art level among the dopant‐free metal phthalocyanines HTL‐based PSCs. Abstract : Copper(II) 2, 3, 9, 10, 16, 17, 23, 24‐octakis((4‐(bis(4‐methoxyphenyl)amino)phenyl)ethynyl)phthalocyanine (8TPAEPC) with high‐carrier mobility of 3.12 × 10 −3 cm 2 V −1 s −1 is synthesized to extend the photovoltaic response of perovskite to 850 nm. The target perovskite solar cells (PSCs9 are qualified with increased power conversion efficiency (PCE) from 20% to 22.10%. Meanwhile, PCE of the PSCs with 8TPAEPC dopant‐free hole transport layer (HTL) reaches 20.42%, which reaches state of the art level among the dopant‐free metal phthalocyanines HTL‐based PSCs.